Strategies for Legally Reducing Tax Liabilities - Azima, Razy Ulul; Famela, Zafia Intan; Pahala, Indra; Wahono, Puji (The Future of Education Journal, 2025)
This article discusses various legal methods that taxpayers can use to reduce their tax burden through tax planning. Tax is a mandatory and coercive payment used for national development. Tax planning is essential for minimizing tax liabilities in accordance with applicable regulations, as taxes can reduce a company’s net profit and cash flow. The primary objective is to save on taxes and reduce the amount of tax paid, as long as it is done legally and without violating tax laws. Strategies such as securing business contracts, optimizing tax credits, applying for a reduction in Article 25 income tax installments, and deferring or paying taxes in installments are discussed. These methods serve as initial steps in effective tax management. They help maintain operational efficiency and ensure compliance with tax regulations. It is crucial to adhere to tax laws to avoid penalties or fines.